The Preferences of Consumers’ Halal Products in Cosmetics Market - Mahliza, Febrina; Prasetya, Prita; Kuswibowo, Christian (Universitas Prasetiya Mulya, 2023)
The various challenges faced by local industries have limited them performance in serving the halal market. This study aims to review consumer challenges and concerns, especially in consuming halal cosmetics. The development of a research model related to the determinants of halal products in the context of halal cosmetics products are important as a reinforcement of previous research. Therefore, this study aims to review the determinants of consumers in consuming halal products. Surveys through questionnaires are conducted by researchers to collect respondents to answer and the collected data is analyzed by quantitative research methods. A total of 150 questionnaires were coded and analyzed by statistical techniques. This research contributes to an understanding of how consumers view the sustainability of the consumption of Halal cosmetic products. Based on the results of the study, religiosity had no significant effect on behavior. Halal knowledge has no significant effect on behavior. Attitude has a positive and significant effect on behavior. Lifestyle has a positive and significant effect on behavior.